UiTM Perak landscape architecture students clinch gold award at International Art Jamming Competition 2024 / Muhammad Falihin Jasmi - Jasmi, Muhammad Falihin (Universiti Teknologi MARA, Perak, 2024)
Kuala Langat, 26th May 2024 – The PIKASO team from UiTM Perak has secured the prestigious Gold Award at the International Art Jamming Competition 2024, hosted jointly by Gamuda Parks, Gamuda Cove, and Universiti Teknologi MARA (UiTM). The team of emerging artists from the Landscape Architecture Programme, Muhammad Nazmy Azhary bin Mohd Nazry, Muhammad Amri Fikri bin Noor Azman, and Khaleeda binti Mohd Khair, supervised by LAr. Dr. Zulkefle Hj Ayob, claimed the top honour along with a cash prize of RM5,000 and Gamuda Play tickets. Their artwork titled “ChromaWild,” distinguished by its vibrant colours and innovative concept, captivated both the jury and the public at the event.